(untitled) (Development Service Industry Management, 2024)
The study focuses on the management processes of enterprise development based on innovation. It is shown that the development of the enterprise concerns the improvement of basic characteristics - indicators of the state and dynamics of the main parameters in all functional areas. For such purposes, a systematic and complex policy is implemented, which provides for a wide range of measures in various spheres of the economy and management of business development and its production and economic elements. However, it is the innovative type of development that is, firstly, the most effective and has the greatest return; secondly, it is the innovative approach that allows you to simultaneously influence most of the growth parameters and achieve high stability in this on the basis of the inevitability of extended reproduction both in production and in the market positions of the enterprise. The purpose of the article is to develop a methodology for identifying and forming the composition of indicators, as well as summarizing their role in the management system of innovative processes at the enterprise. In accordance with the set goal, the composition of indicators - indicators and criteria of innovative development was defined and formed; developed a methodology for forming the composition of indicators; the role of selected criteria in reflecting the course of processes of innovative development of the enterprise is determined. The stages of management of innovation processes at the enterprise are defined, in particular (1) preparation and planning of innovation development, (2) assessment of innovation potential, (3) decision-making in the field of innovation, (4) development and implementation of innovations, (5) evaluation of the results of innovation progress, (6) expanding the spheres of innovative development. Indicators of management of innovative processes at the enterprise include: a) economic effect of innovative activity; b) scientific and technical result of innovative progress; c) social effect of innovative activity; d) environmental consequences of innovative development.